Infected total knee arthroplasty due to postoperative wound contamination with Pasteurella multocida. (9th October 2013) - Subramanian, Bala; Holloway, Edward; Townsend, Robert; Sutton, Paul
Abstract : Pasteurella multocida is a small Gram-negative bacterium comprising part of the normal gastrointestinal and nasopharyngeal flora of domestic pets, such as dogs and cats. It rarely causes infection in humans. Previous reports of P multocida causing prosthetic joint infection have described either haematogenous spread of infection from a distant site through a scratch or bite, or reactivation of infection from a previous injury. We report a case of acute total knee arthroplasty joint infection becoming acutely infected by P multocida . We postulate that the mechanism of infection was direct contamination of the wound as a consequence of the patient being licked by his pet dog. We discuss the potential role played by thromboprophylaxis as a factor contributing to prolonged wound leak.